2009
DOI: 10.1080/09544820903158835
|View full text |Cite
|
Sign up to set email alerts
|

Capturing users’ perceptions of valuable experience and meaning

Abstract: In this article, we argue that more 'fit-to-user' products can be designed by understanding the underlying influential factors of user experience. Those factors go beyond the functional needs of the user, and thus, more 'fit-to-user' products can be designed. This is especially important as technology becomes more and more ubiquitous and its usage is only task-and work-related. Usability-related goals of design for devices to be used in leisure and fun activities are not enough to evoke positive emotions and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 20 publications
2
19
0
1
Order By: Relevance
“…According to Boztepe (Boztepe, 2007), value as experience is created as a result of the interaction between what the product provides and what the users bring in terms of their goals, needs, limitations, etc. Previous studies in this field argue for understanding how values change over time (Parasuraman, 1997), (Boztepe, 2007), (Nurkka et al, 2009). Our results support these claims with field evidence, and provide a lively and detailed account of participants' experiences, based on ethnography, strengthening an approach that does not predominate in ICTD research.…”
Section: Discussionsupporting
confidence: 79%
“…According to Boztepe (Boztepe, 2007), value as experience is created as a result of the interaction between what the product provides and what the users bring in terms of their goals, needs, limitations, etc. Previous studies in this field argue for understanding how values change over time (Parasuraman, 1997), (Boztepe, 2007), (Nurkka et al, 2009). Our results support these claims with field evidence, and provide a lively and detailed account of participants' experiences, based on ethnography, strengthening an approach that does not predominate in ICTD research.…”
Section: Discussionsupporting
confidence: 79%
“…This need is emphasised by both Visser et al (2011) and Nurkka et al (2009) in their discussions of design for social connectedness and user value perception. Further, the need for support in this domain is particularly significant because of the complexity and variety of unconscious strategies available to the designer (Abrahamsen, Steg, Vlek, & Rothengatter, 2005;De Young, 1993).…”
mentioning
confidence: 99%
“…The preliminary results of sentence completion use in Case Study 1 and 2 have been published in Kujala and Nurkka (2009) and Walsh et al (2010) respectively. We have also applied sentence completion for identifying needs and values related to computer usage in a parallel case study published in Nurkka et al (2009 The first sentences were developed relating to user needs and values associated with user experience (Hassenzahl et al, 2010;Kujala and Väänänen-Vainio-Mattila, 2009). As Hassenzahl et al (2010) showed, the fulfillment of universal psychological needs is the major source of positive experience with products; accordingly they described universal psychological needs as competence, relatedness, popularity, stimulation, meaning, security, or autonomy.…”
Section: Methodsmentioning
confidence: 99%